Stage IVB ovarian carcinosarcoma in BRCA wild-type patients: two case reports of unexpected long-term remission - De Tommasi, Orazio; Bigardi, Sofia; Guerriero, Angela; Tasca, Giulia; Massa, Davide; Spagnol, Giulia; Nardin, Margherita; Noventa, Marco; Saccardi, Carlo; Tozzi, Roberto (Frontiers in Oncology, 2026)
BackgroundOvarian carcinosarcoma (OCS), also known as malignant mixed Müllerian tumor, is a rare and highly aggressive subtype of epithelial ovarian cancer, accounting for less than 4% of all cases. It typically presents at advanced stages and is associated with dismal outcomes, with a five-year survival rate below 30%. Despite improvements in cytoreductive surgery and systemic therapies, long-term survival in stage IV disease remains exceedingly uncommon.Case presentationWe report two exceptional cases of stage IVB Müllerian carcinosarcoma occurring in BRCA wild-type postmenopausal women who achieved prolonged complete remission exceeding five years after multimodal management. The first patient, aged 61, presented with bilateral adnexal masses and a solitary pulmonary metastasis. She underwent primary cytoreductive surgery including hysterectomy, bilateral adnexectomy, lymphadenectomy, appendicectomy, and omentectomy, followed by six cycles of platinum-taxane chemotherapy. Residual pulmonary disease was later removed via video-assisted thoracoscopic lobectomy, confirming metastatic OCS. Post-recurrence, she received off-label maintenance with tamoxifen 20 mg daily for five years and remains disease-free at 70 months. The second patient, aged 70, presented with a pelvic mass invading the recto-sigmoid wall and a synchronous hepatic metastasis. She underwent extensive cytoreductive surgery including hysterectomy, en-bloc rectal resection, lymphadenectomy, cholecystectomy, and liver wedge resection, achieving complete macroscopic cytoreduction. Histology confirmed a Müllerian carcinosarcoma with a predominant endometrioid component. Postoperative chemotherapy with carboplatin-paclitaxel was followed by maintenance niraparib 100 mg twice daily for three years. She remains in complete remission at 60 months.DiscussionBoth patients demonstrate durable disease control in the absence of germline or somatic BRCA mutations, suggesting that long-term remission may be achievable even in BRCA-wild-type OCS through optimal surgery and individualized maintenance approaches. Tamoxifen, rarely employed in this setting, may have provided estrogen-receptor-mediated tumor suppression in the first case, while the second case highlights potential activity of PARP inhibition beyond BRCA mutation carriers.ConclusionThese two reports challenge the long-held perception of uniformly poor outcomes in metastatic ovarian carcinosarcoma. Complete cytoreductive surgery combined with tailored systemic and maintenance therapies can achieve sustained remission even in advanced-stage BRCA-wild-type patients. Broader molecular profiling and international collaboration are essential to refine management strategies for this rare and aggressive malignancy.